2011
DOI: 10.1016/j.pain.2010.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Workers’ perspectives on low back pain recurrence: “It comes and goes and comes and goes, but it's always there”

Abstract: Although various measures of low back pain (LBP) recurrence have been proposed, none have been tested to determine if they are consistent with what those with LBP perceive a "recurrence" to be. To further the understanding of LBP recurrence and how to measure it, we examined how individuals with a history of LBP describe their back pain experiences. A qualitative approach was chosen and six mixed-gender focus groups were conducted. Discussions were facilitated by two researchers and structured around predeterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 17 publications
2
77
1
3
Order By: Relevance
“…The number of focus groups and participants were close to published focus group studies [29]. This study was conducted by rheumatologists, while most studies in this field are conducted by psychologists: in a recent review of qualitative studies on LBP [4], only one [18] of the 33 studies [5][6][7][8][9][10]13,[19][20][21][22][23]32] was conducted by physicians. Thus, some aspects of experiences of LBP could have been under-evaluated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The number of focus groups and participants were close to published focus group studies [29]. This study was conducted by rheumatologists, while most studies in this field are conducted by psychologists: in a recent review of qualitative studies on LBP [4], only one [18] of the 33 studies [5][6][7][8][9][10]13,[19][20][21][22][23]32] was conducted by physicians. Thus, some aspects of experiences of LBP could have been under-evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…As defined by the World Health Organisation, this condition is accepted as a biopsychosocial phenomenon in which anatomical injury interplays with other factors [2]. Beyond pain and disability, psychological and social aspects have a significant impact on living with chronic LBP [3][4][5][6][7][8][9][10][11][12]. Mental aspects of chronic LBP are related to psychological distress, in particular anxiety and depression [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Young, Wasiak, Phillips, and Gross (2011) was distinctive in that most participants were still working. For them, periods of relative normality were interrupted by periodic flare-ups and sudden attacks ('I bent over to pick up the walker, then whamo… I didn't think I was going to walk again after that experience', p. 207).…”
mentioning
confidence: 99%
“…Studies have shown that patients who accepted this reality were better able to cope with the condition (Strong and Large1995;Wade 2003). However, patients have adopted various methods for managing LBP, such as avoiding certain postures, not participating in certain activities, prioritising activities and faith (Bowman 1994;Strong and Large1995;Skelton et al 1996;Ong et al 2004;Busch 2005;Young et al 2011). Coping with CLBP Stigma Changing outlook Based on data from ; Froud et al (2014) Several factors influence patients' ability to cope with CLBP, including culture and beliefs (Wade 2003;.…”
mentioning
confidence: 99%